2020
DOI: 10.1038/s41588-020-0639-9
|View full text |Cite
|
Sign up to set email alerts
|

TETs compete with DNMT3 activity in pluripotent cells at thousands of methylated somatic enhancers

Abstract: Mammalian cells stably maintain high levels of DNA methylation despite expressing both positive (DNMT3A/B) and negative (TET1-3) regulators. Here, we analyzed the independent and combined effects of these regulators on the DNA methylation landscape using a panel of knockout human embryonic stem cell (ESC) lines. The greatest impact on global methylation levels was observed in DNMT3-deficient cells, including reproducible focal demethylation at thousands of normally methylated loci. Demethylation depends on TET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 68 publications
4
88
0
Order By: Relevance
“…Nevertheless, although we observed significant changes in DNA methylation and gene expression, in SSc CD4+ T cells, we cannot conclusively speculate on the effects these alterations have in regard to chromatin accessibility and structure without further validation in patients. However, previous studies do show a direct correlation between DNA methylation and chromatin states [86][87][88]; therefore, it is possible that chromatin structure is also altered in SSc CD4+ T cells.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, although we observed significant changes in DNA methylation and gene expression, in SSc CD4+ T cells, we cannot conclusively speculate on the effects these alterations have in regard to chromatin accessibility and structure without further validation in patients. However, previous studies do show a direct correlation between DNA methylation and chromatin states [86][87][88]; therefore, it is possible that chromatin structure is also altered in SSc CD4+ T cells.…”
Section: Discussionmentioning
confidence: 85%
“…TET1 seems to exclude DNMT3A1, the longer isoform of DNMT3A, from proximal promoters and canyons where TET1 seems to preferentially bind in embryonic stem cells (Gu et al, 2018 ). Moreover, it was shown that TET proteins compete with DNMT proteins to regulate the methylation status of enhancers (Verma et al, 2018 ; Charlton et al, 2020 ).…”
Section: Mechanisms Of Tet Functionmentioning
confidence: 99%
“…The latter requires the involvement of ten-eleven translocation proteins (TET1, TET2, and TET3) and the activation-induced deaminase [ 22 ]. DNA methylation leads to gene silencing by arresting the binding of transcriptional factors or by chromatin remodeling, and its dynamics is involved in diverse biological processes [ 23 25 ]. Thus, DNA methylation plays a vital part in stem cell differentiation, development, and disease by regulating genes [ 26 28 ].…”
Section: Epigeneticsmentioning
confidence: 99%